2018
DOI: 10.1016/j.jnutbio.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between red wine and isolated trans-resveratrol on the prevention and regression of atherosclerosis in LDLr (−/−) mice

Abstract: Moderate consumption of red wine has been widely associated with reduced cardiovascular risk, mainly due to its composition in phenolic compounds with antioxidant activity, such as resveratrol. The objective of this study was to compare the effect of red wine vs. trans-resveratrol consumption on the prevention and regression of atherosclerosis in LDLr mice. This study consisted of two protocols: "Prevention" (PREV) and "Regression" (REGR). Both protocols included four groups: red wine (WINE), dealcoholized red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…According to recent studies, resveratrol mainly improves three important characteristics of macrophages that are related to atherosclerosis, including the ability to efflux cholesterol, formation of foam cells and release of proinflammatory mediators [31,35,41,42,[44][45][46]. Our results suggest that resveratrol inhibits monocyte recruitment at least in part by inhibition of IL-1β release in macrophages, with the lower IL-1β release likely the result of enhanced RCT.…”
Section: Discussionsupporting
confidence: 52%
“…According to recent studies, resveratrol mainly improves three important characteristics of macrophages that are related to atherosclerosis, including the ability to efflux cholesterol, formation of foam cells and release of proinflammatory mediators [31,35,41,42,[44][45][46]. Our results suggest that resveratrol inhibits monocyte recruitment at least in part by inhibition of IL-1β release in macrophages, with the lower IL-1β release likely the result of enhanced RCT.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have indicated the beneficial effects of sirtuins as the best small molecule that activate sirtuins, which extended lifespan in a yeast model [104][105][106][107][108][109]. Although only the longevity extension effect of resveratrol has been reported in C. elegans and D. melanogaster, many subsequent studies reported that resveratrol intake promotes health and plays a preventive role in age-related diseases, such as cancer [110][111][112][113], atherosclerosis [114,115], arthritis [116,117], cataract [118][119][120], cardiovascular disease [121], hypertension [122,123], type 2 diabetes [124][125][126][127], osteoporosis [128][129][130], and Alzheimer disease [131][132][133]. In clinical studies, resveratrol intake improved the memory capacity of elderly individuals and reduced blood lipid levels in obese and type 2 diabetic patients [134,135].…”
Section: Resveratrolmentioning
confidence: 99%
“… 2017 ; Chassot et al. 2018 ). Interestingly, previous research have revealed that rutin possess good hypocholesterolemia and antioxidant effects, and can be found in various herbal medicines with hypocholesterolemia and antioxidant properties (da Silva et al.…”
Section: Discussionmentioning
confidence: 99%